Processing and characterization of thermoplastic corn starch‐based film/paper composites containing microcrystalline cellulose. (4th September 2021) - Chen, Jie; Long, Zhu; Dou, Chang; Wang, Xia; Meng, Yahui
Abstract: BACKGROUND: Different thermoplastic starch (TPS) films were prepared with or without the addition of microcrystalline cellulose (MCC) obtained via the melt‐extrusion method, and then the hot‐press method was used to produce environmentally friendly TPS‐based film/paper composites to replace petroleum‐based materials. RESULTS: The paper–plastic composites exhibited good interfacial adhesion from the scannign elctron microscopy images. It was seen that 5 wt.% MCC was added to reinforce the mechanical properties of TPS films, such that it also improved the barrier properties of MCC@TPS/paper composites and extended the path of water vapor through TPS films, which decreased the water vapor transmission rate of MCC@TPS/paper composites. TPS/paper composites and MCC@TPS/paper composites have better physical properties (i.e. smoothness, flexibility and folding resistance) than only paper. In particular, it was found that the water contact angle of MCC@TPS/paper composites and TPS/paper composites were higher than single‐layer paper. Furthermore, MCC reinforced paper–plastic composites demonstrated good barrier properties which can meet the requirement of the need for lower water sensitive materials in the food packaging industry. CONCLUSION: Thermoplastic corn starch‐based film/paper composites have good application properties as a potential source of bioplastic materials. © 2021 Society of Chemical Industry.